Pattern of dermatophyte in Bangabandhu Sheikh Mujib Medical University (Bangladesh Journal of Medical Microbiology, 2012)
Dermatophytes are by far the most significant fungi because of their widespread involvement of population at large and their prevalence all over the world. This is an attempt to observe the spectrum of dermatophytes among the clinically suspected cases of dermatophytosis attending the outpatient department of Dermatology and Venereology, Bangabandhu Sheik Mujib Medical University, Dhaka. Three hundred and twenty clinically suspected cases of dermatophytosis were subjected to mycological studies. One hundred and five cases (32.8%) were positive for fungus in direct microscopy while 97(30.3%) were culture positive. Tinea unguium was the most common clinical type encountered followed by tinea corporis. Dermatophytosis was more common in the age group of 21-30 years. The male to female ratio was 1.54:1. Trichophyton rubrum 84(86.6%) was found common etiological dermatophyte species followed by Trichophyton mentagrophytes 8(8.2%) and Epidermophyton floccosum 5(5.2%).DOI: http://dx.doi.org/10.3329/bjmm.v6i2.19370 Bangladesh J Med Microbiol 2012; 06(02): 11-14